Fungal leaf spot diseases of mango (Mangifera indica L.) in Southeastern Nigeria and biological control with Bacillus subtilis - Ralph N. Okigbo; Maria I. Osuinde (Plant Protection Science, 2003)
The incidence of fungal leaf spot diseases on mango (Mangifera indica) in Southeastern Nigeria and application of a biological control measure was investigated. The survey proved that the incidence of leaf spot diseases was greatest in Umuahia (72%) followed by Okigwe and Ojoto, with a peak at the beginning of the rainy season (February-March). Three pathogenic fungi, Pestalotiopsis mangiferae, Botryodiplodia theobromae and Macrophoma mangiferae, were isolated from leaf spots. Other fungi, Fusariella spp., which are well known saprophytes of dead plant materials, and the fungus Meliola sp., were also isolated from diseased leaves. Pathogenicity tests showed that P. mangiferae, B. theobromae and M. mangiferae were the causal agents of the fungal leaf spot diseases. Symptoms developed 5 weeks after inoculation of healthy leaves. Bacillus subtilis NCIB 3610, isolated from soil under a mango tree, inhibited P. mangiferae, B. theobromae and M. mangiferae by 57%, 61% and 58% respectively on agar plates. Also, in in vivo experiments the symptoms were considerably reduced in the field by the application of the antagonist. The importance of the biological control method for rural mango farmers is emphasised.